PRECIPITATION AT SYOWA STATION - ワダ, マコト; アオキ, シュンジ; セコ, カツモト; マツバラ, コウジ; ドイ, モトヒサ; ウエクボ, テツロウ; オカダ, ケンジ; カワグチ, サダオ; WADA, Makoto; AOKI, Shuhji; SEKO, Katsumoto; MATSUBARA, Kouji; et al. (National Institute of Polar Research, 1991)
P(論文) A 5-year project of "Antarctic Climate Research (ACR)" has been started from JARE-28 in 1987. Observations of clouds and precipitation were carried out using vertical pointing radar and two microwave radiometers in 1988 (JARE-29), the second year of this project. The observations of vertical pointing radar were begun on February 24,1988,and the microwave radiometers observations were handed over to JARE-29 by JARE-28 on February 1,1988. The characteristics of the precipitation in 1988 at Syowa Station, on the coast of Antarctica, are described in this paper. Ten days variation of precipitation are calculated using radar echo intensity at 300m altitude and the relation between radar reflectivity factor (Z) and rainfall rate (R), the so-called Z-R relation. The values obtained from this method are free from the contamination of drifting snow which affects precipitation obtained by rain gauge. The result shows the maximum precipitation in autumn (February and March) and the minimum precipitation in spring (September and October). Low precipitation in spring seems to be characteristic of 1988 at Syowa Station. Snow crystals of precipitation there can be classified into three types : graupel or a heavily rimed crystals, grathering bullets, and other types of crystals such as snowflakes, dendrites and plates. The first and second types of crystals were mainly observed throughout 1988. The height of the radar echo was relatively low; namely, the echo top was under 2km in altitude, in the period when the first type of crystals mainly fell. On the other hand, in the period when the second type of crystals mainly fell, the echo top was often over 4km altitude. departmental bulletin paper